Influence of storage time and temperature on the activity of urease - YARAT, AYŞEN (My University, 2019)
Enzymes are made of protein, that is why they are sensitive molecules and are affected by storage conditions. A small change in enzyme activity during storage may cause a big error in analysis results. The aim of the study was to evaluate the effects of storage time and temperature on urease activity. Urease solutions were prepared at different activities (from 100 to 2000 U/mL) and stored at room temperature, in the refrigerator (4°C), and in the deep freezer (-18°C and -80°C). Activity measurements were made at regular intervals until 28 days by the modified Weatherburn method. The relative activities of 100-1000 U/mL urease solutions stored at room temperature, 4, -18 or -80°C were 75% and below after 4 days. Twenty-eight days later, for 2000 U/mL urease solutions, only at room temperature, the relative activity was reduced to 37%, while at 4, -18 or -80°C, the relative activities were above 80%. Since urease can be maintained at 4°C for 28 days without significant loss of activity, it has practical importance. Low-activity urease solutions (such as 100-1000 U/mL) should not be stored at -18 or -80°C for short or long term storage, they should be stored at 4°C only for one day. Keywords: Urease activity, storage time, storage temperature